Poda e raleio da pimenteira para produção e qualidade de frutos - Marchi, Luana Ferreira (Universidade Federal de São Carlos, 2018)
Peppers are an important fruit vegetable, valued by farmers for their profitability and by consumers for their sensorial characteristics. Its production can be influenced by the management of the plant, through the number of stems and thinning of the fruits, aiming at quality and value aggregation. In this sense, the objective of this work was to evaluate the production, productivity and biometry of the fruits of the CCA 37701 strain of non-pungent (sweet) pepper cultivated in a protected environment through pruning of stems and fruit thinning. The experiment was carried out at the Agricultural Sciences Center of UFSCar-Araras-SP under a randomized block design, with four replications in a 2 x 2 pruning scheme (without pruning and pruning of the stems) and thinning (without thinning and thinning) of fruits). Four plants of each experimental plot were evaluated over eight harvests. The evaluated characteristics were: total number of fruits, total fruit mass, total average fruit mass, total productivity, number of commercial fruits, number of defective fruits, commercial fruit mass, average commercial fruit mass, percentage of commercial fruits , fresh mass of 10 fruits, dry mass of 10 fruits, percentage of dry mass, length, diameter, length / diameter ratio, fruit pulp thickness, number of loci, soluble solids content, pH, titratable total acidity and maturation. The data collected were submitted to analysis of variance and the means compared by the Tukey test. There was a significant interaction between the treatments for mean mass of total fruits, commercial fruit mass, average commercial fruit mass, percentage of fruit dry mass, average diameter, length / diameter ratio, titratable total acidity and maturation index. The treatments conducted with pruning, regardless of whether the fruits were thinned, provided higher total mass and diameter, but reduced the commercial mass. Therefore, pruning management is recommended to increase the average fruit mass and the diameter, and it can be used for the commercialization of fresh fruits.
Prunning and thinning of the pepper for production and fruit quality
Keywords: Manejo; Produtividade; Sistema de condução; Handling; Productivity; Driving system; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA